PENGARUH LATIHAN ATHLETIC BASIC COORDINATION (ABC) RUNNING TERHADAP KETERAMPILAN LARI PELAJAR - Aristiyanto Aristiyanto; Guntur Ratih Prestifa Herdinata; Sahrul Prasojo (Jurnal Sporta Saintika, 2021)
Abstract This study aims to determine the effect of ABC running training on improving the running skills of student athletes in Semarang Regency. This study used a correlational quantitative research type with a descriptive approach using a quasy experiment method. The population of the study was all student athletes in Semarang Regency with a sample of 20 people. The instrument used was a running technique analysis. The data analysis technique used is the t test (paired sample t-test). The results of data analysis indicate that there is a significant effect of ABC running training on the skills of student athletes in Semarang Regency. The t test results obtained by the value of P = (0.000) <α (0.05), so there is a significant increase in the skills of student athletes in Semarang Regency. the percentage increase of 15.61%. This means that the ABC running training method can improve running skills for student athletes in Semarang Regency. Keywords: training, athletic basic coordination, skill, sprint